2008
DOI: 10.1038/oby.2008.214
|View full text |Cite
|
Sign up to set email alerts
|

Motor Skill Performance and Physical Activity in Preschool Children

Abstract: Children with better-developed motor skills may find it easier to be active and engage in more physical activity (PA) than those with less-developed motor skills. The purpose of this study was to examine the relationship between motor skill performance and PA in preschool children. Participants were 80 three-and 118 four-year-old children. The Children's Activity and Movement in Preschool Study (CHAMPS) Motor Skill Protocol was used to assess process characteristics of six locomotor and six object control skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
402
13
63

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(507 citation statements)
references
References 17 publications
29
402
13
63
Order By: Relevance
“…This speculation is supported by earlier studies indicating that time spent outdoors is associated with a higher amount of physical activity (Klesges et al 1990), and a positive relationship between high level of play activities and gross motor skills (Sääkslahti et al 1999). Earlier studies using different measures than ours have indicated weak and conflicting directions in the relationships between FMS and MVPA intensity in this age group (Cliff et al 2009;Fisher et al 2005;Williams et al 2008). For instance, Fisher et al (2005) reported low but significant correlations between MVPA and total motor skill score in young Scottish children, whereas Cliff and colleagues (2009) …”
Section: Relationships Between Motor Skills and Activitysupporting
confidence: 70%
See 1 more Smart Citation
“…This speculation is supported by earlier studies indicating that time spent outdoors is associated with a higher amount of physical activity (Klesges et al 1990), and a positive relationship between high level of play activities and gross motor skills (Sääkslahti et al 1999). Earlier studies using different measures than ours have indicated weak and conflicting directions in the relationships between FMS and MVPA intensity in this age group (Cliff et al 2009;Fisher et al 2005;Williams et al 2008). For instance, Fisher et al (2005) reported low but significant correlations between MVPA and total motor skill score in young Scottish children, whereas Cliff and colleagues (2009) …”
Section: Relationships Between Motor Skills and Activitysupporting
confidence: 70%
“…Motor skills proficiency (Bürgi et al 2011;Fisher et al 2005;Kambas et al 2012) especially locomotor and manipulative skills (Cliff et al 2009;Williams et al 2008), have explained a significant amount of the variance in physical activity levels. It is recognized that FMS proficiency as such, and as a significant correlate of increased physical activity, is a critical health and development determinant.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] On the basis of these previous studies, it has been hypothesized that performance level in motor skills may predict PA. 8, 10 We could not replicate an impact of motor skills on increases in objectively measured PA in young children, but, in contrast, found that higher baseline PA was associated with beneficial changes in motor skills at follow-up. Our data suggest that the relationship between PA and motor skills is dominated by the A cross-sectional and longitudinal study (Ballabeina) F Bürgi et al impact of PA on motor skills.…”
Section: Pa and Motor Skillsmentioning
confidence: 99%
“…9,10 As those studies represent crosssectional data, it is difficult to draw conclusions about the direction of causality. Therefore, prospective data are needed that may help to establish recommendations for strategies in health promotion, especially in younger children.…”
Section: Introductionmentioning
confidence: 99%
“…It seems to be known that motor domain in childhood is inversely associated with the sedentary lifestyle 39 and the improvement of aerobic capacity in adolescents 40 , so it could be a protection for obesity, indirectly. In a finish cohort, Ridgway et al described that early developmental achievements, such as walking or standing without support, were important predictors of sports participation at around 14 years old, as well as increasing their muscle strength and aerobic capacity during adulthood 41,42 .…”
Section: Early Motor Development and Obesitymentioning
confidence: 99%